2021
DOI: 10.1021/acs.jpca.0c10867
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Activation of CO2 via (Mn–CO2) Complex on Magic-Numbered Anionic Coinage Metal Clusters Mn (M = Cu, Ag, Au)

Abstract: Given the immense challenge of excessive accumulation of carbon dioxide (CO 2 ) in the earth's atmosphere, an extensive search is under way to convert atmospheric CO 2 to compounds of more utility. With CO 2 being thermodynamically extremely stable, activation of CO 2 is the first and most important step toward its chemical conversion. Building upon our earlier model for the anionic activation of CO 2 with azabenzene and inspired by the work of others on metal atom−CO 2 complexes, we investigated the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…So the CO 2 •– anion is metastable with a short lifetime of ∼90 ms. , As a result, despite being highly reactive, the direct use of CO 2 •– for further CO 2 fixation has been difficult and scarce . Instead of directly using electrons, another strategy is to use anions or partial negative charges to attack the carbon atom on CO 2 , yielding stable products with carboxylic groups. …”
Section: Introductionmentioning
confidence: 99%
“…So the CO 2 •– anion is metastable with a short lifetime of ∼90 ms. , As a result, despite being highly reactive, the direct use of CO 2 •– for further CO 2 fixation has been difficult and scarce . Instead of directly using electrons, another strategy is to use anions or partial negative charges to attack the carbon atom on CO 2 , yielding stable products with carboxylic groups. …”
Section: Introductionmentioning
confidence: 99%
“…In an aqueous solution of transition metal salts, a CO 2 molecule can be activated by forming a transition metal-CO 2 complex via direct coordination [4,22,[76][77][78]. This can be considered a combination of π electrons transfer to the metal and the oxidative addition of the C-O bond to the metal (Scheme 2) [22].…”
Section: Activation Of Co 2 By Homogeneous Catalystsmentioning
confidence: 99%
“…Catalytic reduction of CO 2 to methanol and other products has been observed with transition metal complexes [22]; it is possible to develop highly active catalysts based on early transition metal complexes. It was found that anionic metal clusters (M n − ) with 1, 2, and 6 atoms formed the activated complex (M n -CO 2 ) − for Cu, Ag, and Au [4]. The activation was a result of a strong interaction between the CO 2 moiety and M n − via the formation of a partial covalent M-C bond with a full delocalization of the electronic charge due to electron transfer from the HOMO of M n − to the LUMO of CO 2 as in metal-CO 2 π-backbonding.…”
Section: Activation Of Co 2 By Homogeneous Catalystsmentioning
confidence: 99%
See 2 more Smart Citations